1999
DOI: 10.1097/00006842-199901000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in Patients With an Automatic Implantable Cardioverter Defibrillator

Abstract: Anxiety in AICD patients seems to be unrelated to traumatic experiences, a finding that casts doubt on pure conditioning models of anxiety. Presumably, a life-threatening cardiac disorder increases the likelihood for catastrophic interpretations of bodily signs, especially in anxiety prone AICD patients. In accordance with cognitive models of panic disorder, this cognitive dysfunction could lead to anxiety and depression levels comparable with those of panic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
3
11

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 27 publications
5
53
3
11
Order By: Relevance
“…Thus, ICD shocks serve as a "sickness scoreboard" where shocks are used to forecast future health. Higher levels of shocks, such as in ICD storm, are interpreted as indicators of an impending catastrophe and lead to heightened anxiety and avoidance behavior, consistent with the findings of Pauli et al 24 The psychological distress following an ICD storm may include aspects of all three theories. The experience of an ICD storm is believed to be particularly alarming to patients with ICDs because they feel helpless in attempting to terminate the shocks and may experience altered consciousness due to insufficient cardiac output.…”
Section: General Theories Of Psychological Adjustment To Implantable supporting
confidence: 77%
See 1 more Smart Citation
“…Thus, ICD shocks serve as a "sickness scoreboard" where shocks are used to forecast future health. Higher levels of shocks, such as in ICD storm, are interpreted as indicators of an impending catastrophe and lead to heightened anxiety and avoidance behavior, consistent with the findings of Pauli et al 24 The psychological distress following an ICD storm may include aspects of all three theories. The experience of an ICD storm is believed to be particularly alarming to patients with ICDs because they feel helpless in attempting to terminate the shocks and may experience altered consciousness due to insufficient cardiac output.…”
Section: General Theories Of Psychological Adjustment To Implantable supporting
confidence: 77%
“…This theory helps to explain some of the divergent findings related to shock available in the literature. For example, Pauli et al 24 examined the anxiety scores of patients with ICDs and found that anxiety was not related to ICD discharges but was highly related to a set of "catastrophic cognitions." Patients with high anxiety scores tended to interpret bodily symptoms as signs of danger and believed that they had heightened risk of sudden death.…”
Section: Psychological Adjustment and The Experience Of Shockmentioning
confidence: 99%
“…Thus, anxiety levels may be related more closely to cognitive concepts than to objectively distressing experiences or medical complications. 12 These cognitive schemata may be both a consequence and expression of anxiety following psychological traumatization by ICD discharges and a premorbid characteristic shown by the patients; however, it could also be that higher anxiety levels and dysfunctional schemata increase the probability of shocks by triggering VT.…”
Section: Catastrophic Fears-a Possible Risk Factor In the Developmentmentioning
confidence: 99%
“…8,9 Some authors 7,10 found a correlation between the number of shocks and anxiety, but others did not. 8,11,12 The latter interpret anxiety symptoms as a consequence of cognitions, especially the fear of dying. 12 A major drawback in these studies is that anxiety symptoms were mainly assessed by self-rating instruments (e.g., Spielberger's state anxiety inventory).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation